How to improve results with extracorporeal shock wave lithotripsy - Michelle J. Semins; Brian R. Matlaga (Therapeutic Advances in Urology, 2009)
Objective: Shock wave lithotripsy (SWL) has greatly revolutionized the treatment of patients suffering from stone disease. There are a number of patient- and device-specific factors that can affect treatment outcome. Herein, we review practices that can increase the likelihood of SWL treatment success. Methods: A systematic literature review was performed to identify studies of SWL treatment parameters. Results: Among the factors affecting the outcome of SWL were patient selection criteria, such as stone burden, stone location, and anatomic features. Additionally, technical aspects of the SWL procedure also can affect outcome; these factors include the acoustic output of the lithotripter, the coupling of the lithotripter to the patient, and the power, total number, and rate of shock wave delivery. Conclusions: The outcome of SWL can be optimized with close attention to patient selection criteria as well as the manner in which the treatment is performed.